Gambaran Komplikasi Kehamilan dengan Penyakit Jantung di RSUD Arifin Achmad Provinsi Riau Periode 2013-2017 - Muhammad Arif Syafei; Donel Suhaimi; Irwan Irwan (Jurnal Ilmu Kedokteran, 2019)
Heart disease is the major non-obstetric cause of morbidity and mortality in pregnancy. Several studies showed that pregnancy with heart diseases are related to maternal and perinatal complications such as mortality, heart failure, arrhytmias, pulmonary oedema, low birth weight, and prematurity. The aim of this study is to know the incidence, characteristic, and complications of pregnancy with heart disease. This study was using descriptive retrospective design with total sampling technique. The sources of data were medical records of patients in January 2013 – December 2017 with number of sample is 37 patients. Cardiac complications was found in 19 (57,6%) cases that was composed of arrhytmias (24,2%), prematurity (21,2%), pulmonary oedema and low birth weight both 15,2%, and heart failure (9,1%).